Colorization-based image coding using graph Fourier transform - Uruma, Kazunori; Konishi, Katsumi; Takahashi, Tomohiro; Furukawa, Toshihiro (Signal processing. Image communication, 2019)
This paper deals with the colorization-based image coding algorithm. In this algorithm, a color image is compressed by encoding its luminance image by a standard coding method such as JPEG coding and by storing several color pixels called as representative pixels (RPs). In decoding phase, a color image is restored from a luminance image and some color information of RPs using the image colorization technique. While previous studies have achieved a high coding performance, the compression method of RPs has not been considered because the positions of RPs are inhomogeneous. In order to improve the image coding performance, this paper proposes the RPs compression algorithm using the graph Fourier transform, where the chrominance image is transformed to graph spectrum and compressed. Using this RPs compression algorithm and a colorization technique, a new colorization-base image coding algorithm is proposed. Numerical results show that the proposed algorithm achieves better performance than some previous studies and JPEG2000 coding.